O transporte público e a circulação urbana em Irati - PR: análise da mobilidade e o direito à cidade - Santos, Rosiléia Alves dos (2012)
The present work is to analyze the problem which makes access to goods for collective use in Irati-PR, from fundamental issues such as circulation, accessibility and mobility in urban space. In this sense, the space is humanized varying forms and uses, society, acting on the space, implying value added. In this perspective it is important to note the lack of transportation planning, public policy clearly seen in the city, for the goods of collective consumption. Resulting in the disparity between social classes, being slightly tied to the ability of each individual to get around to these goods that are essential, such as access to health and leisure. And in a context of need for more urban development, there are more proposals that could improve the current management that addresses the real needs of mobility and accessibility of the entire population.